Intensity modulated radiotherapy (IMRT) in benign giant cell tumors: a single institution case series and a short review of the literature - Röder, Falk; Timke, Carmen; Zwicker, Felix; Thieke, Christian; Bischof, Marc; Debus, Jürgen; Huber, Peter E. (Radiation oncology, 2010)
Giant cell tumors are rare neoplasms, representing less than 5% of all bone tumors. The vast majority of giant cell tumors occurs in extremity sites and is treated by surgery alone. However, a small percentage occurs in pelvis, spine or skull bones, where complete resection is challenging. Radiation therapy seems to be an option in these patients, despite the lack of a generally accepted dose or fractionation concept. Here we present a series of five cases treated with high dose IMRT.